Compritol and Precirol: Innovative Pharmaceutical Excipients - MADGULKAR, A.R.; BHALEKAR, M.; SHIRADKAR, M.R.; DAMLE, M.; RODE, R. (Asian Journal of Chemistry, 2010)
To administer active pharmaceutical ingredients in suitable dosage form they need to be combined with non-medical agents (excipients), which impart the desired properties to the formulation. Since excipients form an integral part of formulation, search for new excipients which can be used in low concentrations and serve multiple functions is always a subject of research. Compritol and precirol are semi-synthetic waxes from the Gelucier wax family. In this review various pharmaceutical applications of compritol and precirol as excipients are highlighted.